Thermo mechanical characteristic of alloy BT 20 with vacuum-plasmatic covering - Ляшенко, Б.А.; Щепетов, В.В.; Мирненко, В.І.; Рутковський, А.В. (Proceedings of National Aviation University (archive), 2004)
Results of the experimental studies are presented in article on and thermocycle creeping of titanium alloy BT20 from vacuum – plasmatic covering TiN, (TiAl)N and (TiC)N in interval of the temperature 350–640 ºС at action of the steady-state load 0.8σв. It is installed the izothermical and thermocycle creeping decreasing of titanium alloy BT20 from vacuum-plasmatic covering.